مدى توافر عوامل الإخلال الوظيفي في مديرية مالية اللاذقية "دراسة ميدانية" - ميّا, علي; داؤد, علا (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدف البحث إلى دراسة مدى توافر عوامل الإخلال الوظيفي لدى الموظفين في مديرية مالية اللاذقية من وجهة نظر الإدارة العليا والمتوسطة (مديرين ورؤساء دوائر ورؤساء شعب), والمتمثلة بـ: الوازع الأخلاقي, الرضا الوظيفي, ضغوط العمل, الثقافة التنظيمية, الثواب والعقاب, ظروف وبيئة العمل. اعتمد البحث على المنهج الوصفي, وشمل مجتمع البحث جميع العاملين الإداريين (مدير, رئيس قسم, رئيس دائرة, رئيس شعبة) في مديرية مالية اللاذقية, والبالغ عددهم (229) إداري, حيث تمّ توزيع الاستبانة عليهم, وتمّ استرجاع (211) استبانة, وبنسبة استجابة بلغت (92.14%). توصل البحث إلى مجموعة من النتائج أهمها: توفر الوازع الأخلاقي, والرضا الوظيفي, والثقافة التنظيمية, وظروف وبيئة العمل بدرجة كبيرة, بينما تتوفر ضغوط العمل وأنظمة الثواب والعقاب بدرجة متوسطة, وجميع هذه العوامل تؤثر بشكل إيجابي على العمل الوظيفي لدى الموظفين في مديرية مالية اللاذقية, وبشكل يؤدي إلى عدم الإخلال الوظيفي. The objective of the study is to investigate the availability of functional impairment factors in the Lattakia Financial Directorate from the point of view of senior and middle management (managers, heads of departments and heads of people), namely: ethical concerns, job satisfaction, work pressures, organizational culture, reward and punishment, . The research community was based on the descriptive approach. The research society included all administrative staff (director, head of department, head of department, head of division) in the Directorate of Finance of Lattakia, (229) administrative, where the questionnaire was distributed to them, 211 answers were retrieved, in response to (92.14%). The research found a number of results, the most important of which are: moral availability, job satisfaction, organizational culture, working conditions and environment, while work pressure and reward and punishment systems are available to a medium degree. All these factors positively affect the work of employees in Lattakia Financial Directorate, In a manner that does not cause any breach of the job.